Cost-effectiveness of contrast-enhanced ultrasound for the detection of endovascular aneurysm repair-related endoleaks requiring treatment - Froelich, Matthias F.; Kunz, Wolfgang G.; Kim, Su Hwan; Sommer, Wieland H.; Clevert, Dirk-André; Rübenthaler, Johannes (Journal of vascular surgery, 2021)
Objective - Follow-up after endovascular aneurysm repair is necessary to detect potentially life-threatening complications such as endoleaks. Computed tomography angiography (CTA) or magnetic resonance angiography (MRA) is often used as standard of care for follow-up. Contrast-enhanced ultrasound (CEUS) has been shown to be a viable and fast real-time nonionizing imaging modality with equivalent diagnostic accuracy while also being superior to color Doppler ultrasound. The aim of this cost-utility analysis was to evaluate the cost-effectiveness of this imaging method in comparison to others for the evaluation of endoleaks requiring treatment. - Methods - A decision model based on Markov simulations estimated lifetime costs and quality-adjusted life years (QALYs) associated with CTA, MRA, CEUS, and color Doppler ultrasound. Model input parameters were obtained from recent literature. The applied sensitivity and specificity values amounted to 90.5% and 100.0% for CTA, 96.0% and 100.0% for MRA, 94.0% and 95.0% for CEUS, and 82.0% and 93.0% for color Doppler ultrasound. Probabilistic and deterministic sensitivity analysis was performed to estimate uncertainty of model results. To evaluate cost-effectiveness, incremental cost-effectiveness ratios were reported as a measure representing the economic value of a strategy compared with an alternative. The willingness to pay was set to $100,000/QALY. - Results - In the base-case scenario for a willingness to pay of $100,000 per QALY, CEUS was the most cost-effective of the four diagnostic strategies with estimated costs of $17,383 and effectiveness of 9.770 QALYs. CTA was estimated to result in lifetime costs of $17,679 with an expected effectiveness of 9.768 QALYs, whereas color Doppler ultrasound showed expected costs of $17,287 with 9.763 QALYs. Expected costs and effectiveness of MRA amounted to $17,945 and 9.771 QALYs each. Base-case estimates of the incremental cost-effectiveness ratios for CEUS vs color Doppler ultrasound equaled $14,173.52/QALY. - Conclusions - CEUS is a cost-effective imaging method for the evaluation of therapy-requiring endoleaks in endovascular aneurysm repair surveillance.
Gesehen am 10.06.2021